A novel maize biochar-based compound fertilizer for immobilizing cadmium and improving soil quality and maize growth. (15th May 2021) - Chen, Zhifan; Pei, Jincheng; Wei, Zhangdong; Ruan, Xinling; Hua, Yanxu; Xu, Wei; Zhang, Chaosheng; Liu, Tianyu; Guo, Yan
Abstract: In this study, a novel biochar-based compound fertilizer (BCF) was synthesized with maize straw biomass, diatomite, triple superphosphate and urea at different temperatures (300 °C, 450 °C, 600 °C) and mixture proportions (5:1:1:x and 10:1:1:x). An investigation was conducted into the effects of BCF at low application rates on the immobilization of available cadmium, soil fertility and maize growth. The lab incubation experiments showed that the low doses of BCF (B5PNx and B10PNx ) contributed to a significant reduction of the Cd availability in soil, with the highest reduction rate of available Cd up to 44.13%. Field experiments demonstrated that the low doses ( < 0.1%) of BCF（especially for B5PN600 ）led to the improvement of soil fertility and maize growth (including maize yield) and the significant reduction of Cd contents in maize grains. The increase of pyrolysis temperature could enhance the biochar adsorption capacity for Cd 2+ by increasing both specific surface areas and total pore volume. The modification of urea, diatomite and triple superphosphate played a vital role on cadmium immobilization, soil improvement and maize growth by forming porous adsorption, precipitates or complexation with the increase of functional groups, as well as supplementation of N, P, Si nutrients. This study suggested that the biochar-based compound fertilizer (BCF with a mixture ratio of 5:1:1:x) produced at 600 °C could be served as a promising and eco-friendly remediation agent for the arable soils polluted with Cd, with reduction of chemical fertilizers. Graphical abstract: Image 1 Highlights: A novel biochar-based compound fertilizer (BCF) with enhanced features was prepared. BCF at low doses can immobilize available Cd and reduce Cd uptake by maize plant. BCF at low doses (<0.1%) plays a beneficial role on soil fertility and maize growth. BCF loaded with diatomite can effectively inhibit Cd translocation. Adsorption capacity is the key factor of biochar on Cd immobilization.